Biosafety: The invisible armour - Abhiruchi Galhotra; Anjan Kumar Giri; Abhisek Mishra (Wolters Kluwer Medknow Publications, 2015)
Growth and advancement of research in life science contributes a lot to improvement in human, plant and animal health. With the emergence of new infectious agents and the threats of bioterrorism, there is a need to handle and manage potentially dangerous micro-organisms and substances used in research. Hence, the issues of Biosafety, Biosecurity, and Biorisk management. While planning for biorisk reduction measures, the whole spectrum of biorisk namely natural occurrences, accidents and deliberate misuse should be taken into consideration. Biological Risk Assessment is an important step for better implementation of biosafety principles, rules and guidelines. A website on biosafety by Department of Bio technology (DBT) reflects national and international guidelines, national rules & procedures with dynamic interaction with Institutional Biosafety Committees (IBSC). National biosafety and bio-waste activities are governed by legislation through State Pollution Control Boards. Despite rules and legislation in place, there are examples of accidents and misuse in research such as- accidentally increasing the virulence of mousepox, synthesis of a poliovirus genome using chemically synthesized oligonucleotides and the map of the polio genome which resulted in a "live" and paralytic poliovirus. The need of the hour is to consolidate the principles and guidelines laid down in already existing rules and to collaborate with other international bodies working for the same purposes so as to strengthen the concepts in every researchers and personnel involved.